Molecular association of Candida albicans and vulvovaginal candidiasis: focusing on a solution - David, Helma; Solomon, Adline Princy (Frontiers in Cellular and Infection Microbiology, 2023)
Candida albicans-mediated vulvovaginal candidiasis (VVC) is a significant challenge in clinical settings, due to the inefficacy of current antifungals in modulating virulence, development of resistance, and poor penetration into the biofilm matrix. Various predisposition factors are molecular drivers to lead to the dysbiosis of normal microflora of the vagina, upregulation of central metabolic pathways, morphogenesis, hyphal extension, adhesion, invasion, and biofilm formation leading to chronic infection and recurrence. Hence, it is crucial to understand the molecular mechanism behind the virulence pathways driven by those drivers to decode the drug targets. Finding innovative solutions targeting fungal virulence/biofilm may potentiate the antifungals at low concentrations without affecting the recurrence of resistance. With this background, the present review details the critical molecular drivers and associated network of virulence pathways, possible drug targets, target-specific inhibitors, and probable mode of drug delivery to cross the preclinical phase by appropriate in vivo models.